Maqashid al-Sharia-Based Accountability in ZIS Accounting Practices: Evidence from BMH Bangkalan - Fahrizal Fahrizal; Ahmad Makhtum; Luluk Hanifah (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2026)
Zakat, infaq, and sadaqah (ZIS) institutions are required to demonstrate accountability not only through financial reporting compliance but also through the realization of Islamic social objectives. However, previous studies have largely emphasized technical compliance with PSAK 109, while the integration of maqashid al-sharia as an accountability framework in ZIS accounting remains underexplored, particularly in local zakat institutions. This study aims to analyze the role of maqashid al-sharia as a basis for accountability in ZIS accounting practices at Baitul Maal Hidayatullah Bangkalan. A descriptive qualitative approach was employed through in-depth interviews, participatory observation, and documentation of financial reports and institutional activities. The findings show that maqashid al-sharia strengthens ZIS accountability by linking financial reporting, transparency, fund distribution, and social programs to the objectives of preserving religion, life, intellect, lineage, and wealth. The institution’s accounting practices are supported by PSAK 109, while its accountability is reflected in educational, da’wah, social-humanitarian, health, and economic empowerment programs for beneficiaries. The novelty of this study lies in positioning maqashid al-sharia as an analytical accountability framework that extends beyond administrative compliance toward social impact and public trust. This study contributes theoretically to the development of maqashid-based Islamic accounting and practically to improving governance, transparency, and accountability in ZIS management institutions.